Role of DJ Stenting in Equivocal Symptomatic Ureteropelvic Junction Obstruction - Khalil, Khansa; Hussain, Khalid; Tariq, Maria; Ahmed, Jawad; Akhtar, Bilal; Tariq, Ali Umair (Biological and Clinical Sciences Research Journal, 2025)
Ureteropelvic junction obstruction (UPJO) is a common cause of renal obstruction, with equivocal symptomatic cases posing diagnostic and therapeutic challenges. Double-J (DJ) stenting serves both as a therapeutic and diagnostic tool, relieving obstruction and clarifying disease severity. However, its efficacy and safety in such cases remain a matter of debate. Objective: To evaluate the clinical and radiological outcomes of temporary DJ stenting in adults with equivocal symptomatic UPJO. Methods: This descriptive single-center study was conducted at Gujranwala Teaching Hospital, Pakistan, from January 2025 to March 2025. Fifty adult patients (18–60 years) with flank pain >3 months, mild to moderate hydronephrosis on ultrasound, and equivocal obstruction on diuretic renogram (T½ 10–20 min) were enrolled. All underwent cystoscopic DJ stent placement for three weeks. Pain scores (VAPS), renal pelvis anteroposterior diameter (APD), and diuretic renogram T½ were recorded at baseline, during stenting, and at 2–6 weeks post-removal. Outcomes were categorized as full response (VAPS < 3 and T½ < 10 min), partial response, or non-response. Data were analyzed using paired t-tests and stratified analyses, with p<0.05 considered significant. Results: The mean age was 34.6 ± 9.5 years, with 66% of patients being male. Baseline VAPS was 7.1 ± 1.2, mean APD 19.6 ± 5.1 mm, and T½ 15.2 ± 2.3 min. At 6 weeks post-removal, mean VAPS improved to 2.3 ± 0.6 (Δ −4.8, p<0.001), APD to 10.4 ± 3.1 mm (Δ −9.2, p<0.001), and T½ to 8.1 ± 1.7 min (Δ −7.1, p<0.001). A full response was achieved in 80% of patients, a partial response in 12%, and 8% were non-responders requiring pyeloplasty. Better outcomes were observed in patients with symptom duration <6 months and preserved baseline renal function. Complications were mild and self-limiting, with no Clavien–Dindo grade 3 or higher events. Conclusion: Temporary DJ stenting is an effective and safe intervention in patients with equivocal symptomatic UPJO, providing significant improvement in pain relief and renal function with minimal complications. Early intervention and careful follow-up optimize outcomes, supporting its role as both a therapeutic and diagnostic strategy in resource-limited healthcare settings.